There’s no app for that! perspectives on engaging diverse communities to promote equitable care - Jennifer Lane; Brittany Barber; Courtney Pennell; Kris Lane; Megan White; Noah Doucette (Digital Health)
Engaging patients and communities in the development and evaluation of mHealth applications can optimize useability, user adherence, health outcomes, and transparency of how personal health data is used, stored, and transferred to commercial partners. This commentary is informed by an event that aimed to invite knowledge sharers/users from equity-denied groups to provide feedback about a preliminary set of questions meant to collect socio-structural health determinants information and their potential use within mHealth applications. Three key lessons were learned: (1) challenges of reciprocity, (2) concerns of responsible data stewardship, and (3) processes of building trust for meaningful community engagement. Responding to historical and ongoing injustices is critical for building trust and supporting successful uptake of health technologies with communities. Soliciting feedback from community once decisions about implementation have been made may come across as performative or disingenuous, further undermining possibilities to establish and maintain productive relationships that are mutually beneficial to all parties involved. Without concerted effort to improve access to healthcare resources, progress made with mHealth applications may come at the expense of people and communities already underserved within existing healthcare systems.